Le nouvel hellénisme hors de ses frontières à partir d’Alexandre le Grand - Pascal Charvet (Cahiers Balkaniques)
Hellenism, beyond borders since Alexander the Great, is considered here from three perspectives. 1) Taking into account the indelible Alexander’s mark on hellenism when he broke the autochtonous frame of Greece in order to diffuse its culture through Orient, as well as the ambiguities generated by this influence and which still supply the analyses of number of intellectuals. 2) Confront the greek vision with the indigenous one: reflect on the hellenistic culture of that period confronting it with the culture of the indigenous countries and nations, Egyptians, Syrians, Indians, especially, in order to determine how these cultures have been adapted and modified, reciprocally, and examine the nature of the link between Alexander’s conquests and their cultural aftermaths. 3) Reflect on our relationship with a fantastic hellenism, affected by the ambiguous mark of Alexander, which has become our invisible and multiform homeland with wich we are still conversing.